The Relationship Between Handwashing Behavior (Ctps) in Covid-19 Prevention Among Elementary School Students in Banda Aceh City - Kausar, Muhammad Anis AL; Santi, Tahara Dilla; Arifin, Vera Nazhira; Fahdhienie, Farrah; Azwar, Eddy (Institute Of Computer Science (IOCS), 2024)
This study investigates the relationship between handwashing behavior, often referred to as Cuci Tangan Pakai Sabun (CTPS), and the prevention of COVID-19 among elementary school students in Banda Aceh City. The research conducted a descriptive-analytic study using a cross-sectional approach. Data was collected from elementary school students in SD Negeri 59 Banda Aceh, with a total sample size of 62 students. The analysis of the data involved both univariate and bivariate analyses. The findings revealed a significant relationship between students' knowledge about COVID-19 and their handwashing behavior, with a p-value of 0.001. Additionally, the role of teachers was found to be significantly associated with students' handwashing behavior, with a p-value of 0.020. However, the study did not establish a significant relationship between media involvement and handwashing behavior, as indicated by a p-value of 0.071. These results align with previous research and highlight the crucial role of knowledge and teachers in influencing proper handwashing behavior among students. In the context of COVID-19 prevention, the study underscores the importance of education, both from teachers and through media, to raise awareness and promote the practice of handwashing with soap (CTPS) as an integral part of preventive measures. Further research is needed to explore additional factors that may impact students' handwashing behavior and to gain a deeper understanding of the potential role of media in shaping this behavior.